2014
DOI: 10.1111/jog.12383
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of laser vaporization for vaginal intraepithelial neoplasia following hysterectomy due to premalignant and malignant lesions

Abstract: Laser vaporization may be a useful option for the treatment of VAIN after hysterectomy. However, a follow-up is required to assess the long-term efficacy of laser treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 29 publications
(41 reference statements)
3
31
1
3
Order By: Relevance
“…HPV clearance could decrease the risk of recurrent disease. HPV persistence after laser vaporisation has been in previous studies 23–62% . In our study, HPV persistence after laser vaporisation was 67%.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…HPV clearance could decrease the risk of recurrent disease. HPV persistence after laser vaporisation has been in previous studies 23–62% . In our study, HPV persistence after laser vaporisation was 67%.…”
Section: Discussionsupporting
confidence: 69%
“…Efficacy rates have been similar to that of laser vaporisation also with regard to recurrence rates, but adverse effects including chronic ulcerations after 5‐fluorourasil have been more common . Previous studies have reported 46–86% cure rates after one laser vaporisation treatment round . Our result of 70% complete histological regression with imiquimod and 90% with laser treated patients can be considered equally effective as conventional laser vaporisation.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Other studies only considered histologically confirmed VAIN as relapse. A Chinese study among 28 patients with VAIN after hysterectomy (group 1) and 11 patients with VAIN due to cervical cancer (group 2) treated with laser vaporization found a regression rate of 85.7 % in group 1 and 54.5 % in group 2 [19].…”
Section: Discussionmentioning
confidence: 98%